5- Gender, Ethnicity and Violence and Their Effects on Livelihoods in the Niger Delta Region, Nigeria: The Case of Keegbara-Dere (Ogoni) and Bolo (Okrika) in Rivers State - Yomi Oruwari; Opuenebo Owei; Margaret Jev (Africa Media Review, 2004)
The Niger Delta Region in Nigeria considered the oil mineral producing area in the country has become a breeding ground for various forms of violence. The inability of residents in these areas to directly gain appreciably from the resources generated by the exploration and exploitation of this natural resource has contributed to this problem. Although it is now recognized that violence severely undermines broader development goals of growth and sustainability, a lot of policy research is dominated by quantitative methodologies. While obviously important, such highly quantitative methodologies fail to capture how people actually experience violence and also how it had impeded their livelihoods. This study, while placing a lot of emphasis on qualitative methodology looks at the interrelationship between ethnicity and violence and their effect on livelihood (on gender basis) in oil mineral producing areas in Nigeria.